INFLUENCE OF IMPROPER PLAY WITH THE CAT ON THE FREQUENCY OF AGGRESSIVE BEHAVIOUR - Wojtaś, Justyna; Garbiec, Aleksandra; Kaleta, Karolina; Decowska, Martyna; Kapustka, Joanna (Polish Journal of Natural Sciences, 2025)
This study aimed to assess the relationship between improperly conducted play and the frequency of aggressive behaviour in cats. The research was conducted using an anonymous survey. Three thousand five hundred respondents with cats took part in the study. Among the animals, 58.9% were individuals aged 1 to 5 years, 24.4% were cats aged 6-15 years, under 14.4% and senior cats over 15 years of age 2.3%. The results were statistically analyzed using the Statistica 13.1 program. Almost half of the respondents confirmed playing with the cat with their hands (42.3%). Aggressive behaviours most often mentioned by caretakers were biting, scratching, attacking hands/legs and attacking other animals. Significant correlations were observed between the occurrence of aggressive behaviour and the way of ending play with the cat. The least aggressive behaviour towards other animals occurred when playing more than three times a day.